A representação adequada no processo coletivo como corolário do devido processo legal - Joao Paulo Alvarenga Brant (2018)
The research seeks to explain the concept of adequacy of representation, imported from the North American legislation. The regulation adopted in class actions has already been applied to the Brazilian collective process, despite the lack of a standard in the integrated system of collective rights. The use, which occurs of lege lata, is object of dissent in the Brazilian doctrine, what makes relevant an analysis as to the possibility of the verification of the adequacy of this representation. According to rule 23 of the US Code of Civil Procedure, fair and adequate representation is one of the requirements for class certification. The theoretical framework is the conception adopted by Antonio Gidi about the definitions of due process of law and its incidence in the interpretation of the collective process. Transferring this concept to the system enforced in Brazil, the question is the possibility of judicial review of the adequacy of representation. Finally, based on constitutional definitions of due process adopted in Brazilian doctrine, it is sought to define the extent and form of applicability, of lege lata, of the requirement of adequacy of representation in the Brazilian collective process.